2021
DOI: 10.3390/toxins13120839
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis: A Common Feature of Immune Cells of Haemodialysis Patients

Abstract: NLRP-3 inflammasome activation can result in interleukin-1β (IL-1β) release and inflammatory cell death (pyroptosis). Caspase-1 is able to trigger both processes. However, other caspases, caspase-4, -5 and -8, are believed to initiate pyroptosis without affecting IL-1 secretion. In this study, we evaluated two cardiovascular risk groups, haemodialysis patients (HD) and patients with intact kidney function but high blood pressure (BP), to analyse the mechanisms driving pyroptosis. Twenty HD were age-, gender- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…NLRP3 inflammasome activation results in caspase-1 activation, in turn causing cleavage of pro-IL-1β and gasdermin D (GSDMD). Active GSDMD aggregates and forms pores in the cell membrane, resulting in cell swelling and a programmed cell death which is called pyroptosis [ 17 ]. Pyroptosis is implicated in the pathogenesis of several neuropsychiatric disorders, such as multiple sclerosis (MS), Alzheimer’s disease, TBI, drug use disorder, and depression [ 18 , 19 ].…”
Section: Nlrp Inflammasomementioning
confidence: 99%
“…NLRP3 inflammasome activation results in caspase-1 activation, in turn causing cleavage of pro-IL-1β and gasdermin D (GSDMD). Active GSDMD aggregates and forms pores in the cell membrane, resulting in cell swelling and a programmed cell death which is called pyroptosis [ 17 ]. Pyroptosis is implicated in the pathogenesis of several neuropsychiatric disorders, such as multiple sclerosis (MS), Alzheimer’s disease, TBI, drug use disorder, and depression [ 18 , 19 ].…”
Section: Nlrp Inflammasomementioning
confidence: 99%
“…Furthermore, we have to keep in mind that caspase-4 activity can also be induced by other molecules. In a recent paper, we demonstrated that caspase-4 activity can be induced by a high concentration (1mmolar) of uremic toxin indoxyl sulfate in the monocytic THP-1 cell line [32]. It seems plausible that if these results can be stably transferred from THP-1 cells to PBMCs of CKD patients, caspase-4 activity can be stimulated by quite different substances.…”
Section: Discussionmentioning
confidence: 89%
“…Besides GSDMD which is a co-executor of pyroptosis, other members of the gasdermin family, including GSDMA3, GSDMB, and GSDME, can also be cleaved to induce pyroptosis [ 6 ]. Studies have shown that caspase-11 and its corresponding proteases, caspase-4 and caspase-5, can trigger pyroptosis by cleaving the pyroptosis executor in the gasdermin protein family [ 86 ]. However, the complete mechanism underlying pyroptosis remains unclear.…”
Section: Effects Of Nlrp3 On Pyroptosismentioning
confidence: 99%